2023
DOI: 10.4143/crt.2023.446
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Plasma Circulating Tumor DNA Sequencing for Precision Medicine in the Management of Solid Cancers

Abstract: Plasma circulating tumor DNA (ctDNA) sequencing has demonstrated clinical utility for tumor molecular profiling at initial diagnosis or tumor progression in advanced solid cancers and is being rapidly incorporated into the clinical practice guidelines, including non–small cell lung and breast cancer. Despite relatively low sensitivity, plasma ctDNA sequencing has several advantages over tissue-based assays, including ease of sampling, rapid turnaround time, repeatability, and the ability to overcome spatial he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 130 publications
0
7
0
Order By: Relevance
“…Previous research has revealed that the concentration of ctDNA in CRC patients can vary depending on the cancer stage and detection methods used. The range has been reported to be between 10 and 1000 ng/µL in some studies [ 17 ], while others have shown it to be between 0.1 and 12 ng/µL. Similarly, the ctDNA concentration in healthy donors has also varied in past studies, ranging from 0 to 100 ng/µL [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has revealed that the concentration of ctDNA in CRC patients can vary depending on the cancer stage and detection methods used. The range has been reported to be between 10 and 1000 ng/µL in some studies [ 17 ], while others have shown it to be between 0.1 and 12 ng/µL. Similarly, the ctDNA concentration in healthy donors has also varied in past studies, ranging from 0 to 100 ng/µL [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, even when accessible, a single biopsy sample may not represent an entire tumor, which usually displays significant spatial heterogeneity. ctDNA-based “liquid biopsies”, on the other hand, do not have some of these drawbacks and can act as a noninvasive cancer biomarker, allowing more frequent and comprehensive analyses of the tumor’s genetic evolution [ 3 , 4 , 5 ]. Two major applications of ctDNA already used in the clinic includd the monitoring of tumor burden before, during, and after treatment and for the detection of post-treatment relapse [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Two major applications of ctDNA already used in the clinic includd the monitoring of tumor burden before, during, and after treatment and for the detection of post-treatment relapse [ 6 , 7 ]. Liquid biopsies have also shown great promise in predicting relapse, progression-free survival, and overall survival across a variety of tumor types and stages [ 3 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, even when accessible, a single biopsy sample may not represent an entire tumor, which usually displays significant spatial heterogeneity. ctDNA-based “liquid biopsies”, on the other hand, do not have some of these drawbacks and can act as a noninvasive cancer biomarker, allowing analyses of the tumor’s genetic evolution more frequently and comprehensively (Cha et al, 2023; Ulz et al, 2017; Kujala et al, 2022). Two major applications of ctDNA already used in the clinic are for the monitoring of tumor burden before, during, and after treatment, and for the detection of post-treatment relapse (Mattox et al, 2019; Ignatiadis et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Two major applications of ctDNA already used in the clinic are for the monitoring of tumor burden before, during, and after treatment, and for the detection of post-treatment relapse (Mattox et al, 2019; Ignatiadis et al, 2021). Liquid biopsies have also shown great promise in predicting relapse, progression free survival, and overall survival across a variety of tumor types and stages (Reinert et al, 2019; Chae et al, 2019; Sanz-Garcia et al, 2022; Cha et al, 2023).…”
Section: Introductionmentioning
confidence: 99%